Criterion-referenced test development : - Shrock, Sharon A. (Pfeiffer, 2007)
Criterion-Referenced Test Development is designed specifically for training professionals who need to better understand how to develop criterion-referenced tests (CRTs). This important resource offers step-by-step guidance for how to make and defend Level 2 testing decisions, how to write test questions and performance scales that match jobs, and how to show that those certified as ?masters? are truly masters. A comprehensive guide to the development and use of CRTs, the book provides information about a variety of topics, including different methods of test interpretations, test construction, item formats, test scoring, reliability and validation methods, test administration, a score reporting, as well as the legal and liability issues surrounding testing. New revisions include: Illustrative real-world examples. Issues of test security. Advice on the use of test creation software. Expanded sections on performance testing. Single administration techniques for calculating reliability. Updated legal and compliance guidelines. Order the third edition of this classic and comprehensive reference guide to the theory and practice of organizational tests today.